Live subtitlers: Who are they? A survey study - Robert, Isabelle S.; Schrijver, Iris; Diels, Ella (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
This article reports on the results of the first study in a larger research project on the profile of the interlingual live subtitler entitled ‘Interlingual Live Subtitling for Access’ (ILSA). Intralingual live subtitling is widely used in the industry and has attracted academic attention. Interlingual live subtitling, on the other hand, is still in its infancy. Although industrial demand is increasing, academic research is lagging behind. Moreover, a competence profile and a subsequent curriculum design are yet to be developed. ILSA wants to bridge this gap. It aims to describe the profile of the interlingual live subtitler and to develop, test and validate a training course for this new professional. This article reports on the initial stage of the project, which consists of a description of the current practice and training of intralingual and interlingual live subtitlers: Who are they and how have they been trained? To answer this question, surveys were disseminated among practitioners. The responses gathered from these surveys not only shed light on the current practices and training programmes; they also demonstrate that an all-encompassing training programme on interlingual live subtitling is lacking. This confirms the belief that projects such as ILSA are needed to support the training of future interlingual live subtitlers and to improve live subtitling in the future.